Arterial Stiffness and Carotid Intima-Media Thickness in Diabetic Peripheral Neuropathy - Avci, Ahmet (Med Sci Monit, 2014)
BACKGROUND: We investigated the relationship between peripheral neuropathy and parameters of arterial stiffness and carotid intima media thickness (CIMT) in patients with type 2 diabetes mellitus (T2DM). MATERIAL/METHODS: The study included 161 patients (80 females and 81 males), 69 of whom had peripheral neuropathy. All patients underwent 24-h blood pressure monitoring, and arterial stiffness parameters were measured. The CIMT was measured using B-mode ultrasonography and patients also underwent transthoracic echocardiographic examination. RESULTS: Patients with peripheral neuropathy, compared with those without it, were older (54.68±8.35 years vs. 51.04±7.89 years; p=0.005) and had T2DM for longer periods (60 vs. 36 months; p=0.004). Glycated hemoglobin (HbA1c) values (8.55±1.85 mg/dL vs. 7.30±1.51 mg/dL; p<0.001), pulse wave velocity (PWV) (7.74±1.14 m/s vs. 7.15±1.10 m/s; p=0.001), CIMT (anterior 0.74±0.15 mm vs. 0.67±0.13 mm; p=0.01), and left ventricular mass (LVM) index (98.68±26.28 g/m(2) vs. 89.71±19.70 g/m(2); p=0.02) were all significantly increased in the group with peripheral neuropathy compared to the group without peripheral neuropathy. We determined that duration of diabetes, HbA1c, and LVM index were predictors of peripheral neuropathy. CONCLUSIONS: A significant relationship was found between diabetic neuropathy and increased PWV, a parameter of arterial stiffness, as well as CIMT, a marker of systemic atherosclerosis. Diabetic peripheral neuropathy may be a determinant of subclinical atherosclerosis in T2DM.